A pilot study on expectation and satisfaction of denture patients in IIUM dental clinic - Ahmad, Norfaezah; Sulaiman, Amizah; Mahidin, Mazmira; Mustaffa, Musliana (Kulliyyah of Dentistry IIUM, 2022)
A patient’s expectations can profoundly affect the satisfaction with a new denture construction. Previous studies have stated that prosthetic treatment failures occur not because of the clinical and technical problems but due to unrealistic expectations of the patient who expects the denture to be comparable to the natural dentition functionally and aesthetically. It is vital to determine the level of patient expectations and educate them so that their expectation could be kept at a reasonable level. In addition, this could ensure high satisfaction with the dental treatment. The objective of the study was to determine the patient expectation and satisfaction before and after denture construction. This research involves 40 patients who received one or a pair of complete dentures at the Kuliyyah of Dentistry, IIUM. The subjects were divided into two groups, a tested and a control group. The tested group received an informational pamphlet and none for the control group. Patients with partial dentition on both arches and patients with severe gag reflex were excluded from this study. The level of expectation and satisfaction of the patient toward the prosthesis was measured by using a self-administered questionnaire. There was no significance differences of expectation and satisfaction shown between the tested and control groups before treatment. However, after a session of denture education by using an informational pamphlet, the level of expectation reduced, and the level of satisfaction increased slightly in the tested group. The use of informational pamphlets during denture education does give a positive impact on the outcome of prosthodontics treatment.